Investigating new drugs from marine seaweed metabolites for cervical cancer therapy by molecular dynamic modeling approach - Sk Injamamul Islam; Sheikh Sunzid Ahmed; Sarower Mahfuj; Gunjan Das; Md. Mohaimenul Islam Tareq; Mazen Almehmadi; Mamdouh Allahyani; Naif Alsiwiehri; Partha Biswas; Md. Nazmul Hasan; Foysal Ahammad (Scientific Reports)
Abstract The etiology of cervical cancer in women is attributed to the continuous infection of the human papillomavirus (HPV). The high costs and side effects of standard treatments and the limited efficacy of HPV vaccination have led to a quest for novel, cost-effective cervical cancer treatments, particularly in middle- and low-income countries. Therefore, our objective was to evaluate the capacity of marine seaweed compounds to hinder the activity of the cervical cancer E6 Oncoprotein. The Seaweed Metabolite Database was evaluated for its ability to inhibit E6 Oncoprotein functions by high throughput virtual screening. The investigations included molecular docking, ADMET test, MD simulation, and MM/GBSA analysis to identify three lead seaweed drug-like compounds: BC008 (-8.9 kcal/mol), RL379 (-8.9 kcal/mol), and BC014 (-8.7 kcal/mol). All of the leading candidates had positive characteristics in terms of pharmacokinetics, pharmacodynamics, and toxicity. The molecular dynamics simulation of the apoprotein, control drug, and lead compounds revealed the superior structural stability and uniformity of the main drug candidates. The MM/GBSA study revealed that the BC008-protein complex exhibited the most significant free binding energy, with a value of -57.41 kcal/mol. In the end, the findings derived from this investigation might provide a basis for developing innovative anticancer treatments.